The problem of terrorism and religious extremism in Kazakhstan, media monitoring in June-August 201 (Journal of Philosophy Culture and Political Science, 2018)
In given article the problems of terrorism and religious extremism based on the Mass media monitoring in June-August, 2011, are considered.